Government coordination mechanism in marine governance: a study on China’s 2023 marine environmental protection law - Li, Xiaoping; Ning, Yu (Frontiers in Marine Science, 2025)
This article explores the tension between the integrity of marine ecosystems and the fragmented administrative systems prevalent in unitary states. Drawing upon the theoretical frameworks of holistic governance, this study investigates the institutional innovations introduced by the MEPL 2023. It conducts a comparative analysis of institutional practices from the European Union’s Maritime Strategy Framework Directive, the Chesapeake Bay Watershed Agreement, and the Arctic MOSPA Agreement. The central focus of the analysis lies in the responsibilities of each department at the central level, the local primacy at the level and a three-tiered responsibility framework encompassing “local primary responsibility, cross-regional coordination, and cross-departmental coordination”, and its role in addressing the fragmentation in marine governance. MEPL 2023 has effectively transformed local governments from passive implementers into proactive collaborators. However, due to ambiguities in the delineation of vertical and horizontal responsibilities and the heterogeneous institutional structures at the local level, significant gaps persist in enforcement. To enhance intergovernmental cooperation, this study proposes targeted strategies from both legislative and enforcement perspectives: clarifying the specific responsibilities of administrative entities at all levels, establishing uniform enforcement standards, creating regional marine management committees, codifying coordinative mechanisms within the draft Ecological Environment Code, and developing a digital platform to support joint monitoring, emergency response, and cross-jurisdictional enforcement. This research provides a replicable and scalable governance model for unitary states within the context of comparative environmental law, aimed at achieving the United Nations Sustainable Development Goal 14.